Grading as a Type of Assessment: statistical analysis and various grading scales - Valdevit, Mirna; Jelaska, Zrinka (2008)
This paper discusses grading in educational system. The first part of the paper shows how grades in schools and universities cover two types of assessment: ordinal and numeric. Ordinal grades show only the rank within a particular class or with respect to criteria of a particular teacher. Numeric grades show numerical relationship and could be viewed as more objective. As the assessment should play an important role in informing L2 students of their progress, the relationship between lexical and numerical grading scales will be analyzed. Examples of grading in various European countries shows that numerical grades are often arbitrary. Therefore arithmetic means should not be applied to them, although that is the practice in many countries that may have practical reasons to assess students progress with only one number or grade. Two Croatian grading cases will be presented to show how various statistical methods have the advantages and disadvantages when grades as the final assessment should be expressed numerically.
Projekt MZOS
Projekt MZOS
ENG